2021
DOI: 10.5114/biolsport.2021.100359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of self-paced high-intensity interval training and moderateintensity continuous training on the physical performance and psychophysiological responses in recreationally active young adults

Abstract: This study aimed to compare the effects of 8-week self-paced high-intensity interval training (HIIT) vs. self-paced moderate-intensity continuous training (MICT) on the physical performance and psychophysiological responses of young adults. Twenty-eight recreationally active young adults (age: 21.1 ± 1.6 years) were randomly assigned to either the self-paced HIIT ( n = 14) or the MICT ( n = 14) group training protocol. The HIIT consisted of two 12–24 x 30 seconds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Along with improving autonomous nervous system and reducing stress, reverse periodization and HIIT have been shown to be more effective in improving athletic performance than traditional programs [21,34]. This result was also found in the present military sample since after the IOT, significant performance improvements were found in the time of 50 and 2000m, and lower limb muscular strength.…”
Section: Discussionsupporting
confidence: 75%
“…Along with improving autonomous nervous system and reducing stress, reverse periodization and HIIT have been shown to be more effective in improving athletic performance than traditional programs [21,34]. This result was also found in the present military sample since after the IOT, significant performance improvements were found in the time of 50 and 2000m, and lower limb muscular strength.…”
Section: Discussionsupporting
confidence: 75%
“…However, chronic studies are necessary to further explore this hypothesis. In this sense, present findings indicate that self-paced HIIT can induce greater physical enjoyment than CT in active young adults [ 44 ].…”
Section: Discussionmentioning
confidence: 86%
“…Meanwhile, HIIT has been alleged as being associated with negative affective responses [ 21 ]. However, exercise preferences and enjoyment vary in the general and clinical populations and some forms of HIIT may be more enjoyable and preferred over MICT for some people [ 22 , 23 ]. Furthermore, a recent, systematic review reported better affective responses during SIT with short sprints (5–6 s) (sSIT) when compared to other training protocols of longer sprints (15–30 s).…”
Section: Discussionmentioning
confidence: 99%